Research on μPMU Configuration Optimization Considering Multiple Operation Modes of Distribution Network - Liang, Zhenfeng; Wang, Jing; Wang, Xiaowei; Zhang, Yining (Frontiers in Energy Research, 2022)
Considering the multiple operation modes of distribution network reconfiguration, a Micro Phasor Measurement Unit (μPMU) configuration optimization scheme considering multiple operation modes is proposed. Firstly, the configuration of μPMU is optimized for each operation mode of the distribution network; secondly, the configuration nodes of each operation mode are clustered and evaluated by K-means according to the shortest distance, and the weights of the four evaluation indexes are determined by AHP-CRITIC subjective and objective combination weighting method. Finally, the node with the highest comprehensive evaluation index is selected as the configuration node. On the basis of considering reconfiguration, the probability of multiple operation modes and the situation of adding a μPMU configuration are introduced; finally, taking IEEE 118 - bus distribution system as an example, the simulation verifies the effectiveness of the proposed method in improving the state estimation of multiple operation modes of distribution network.